2020
DOI: 10.1523/jneurosci.1644-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Voltage-Gated Calcium Channels in Astrocytes during Demyelination Reduces Brain Inflammation and Promotes Myelin Regeneration in Mice

Abstract: To determine whether Cav1.2 voltage-gated Ca 21 channels contribute to astrocyte activation, we generated an inducible conditional knockout mouse in which the Cav1.2 a subunit was deleted in GFAP-positive astrocytes. This astrocytic Cav1.2 knockout mouse was tested in the cuprizone model of myelin injury and repair which causes astrocyte and microglia activation in the absence of a lymphocytic response. Deletion of Cav1.2 channels in GFAP-positive astrocytes during cuprizoneinduced demyelination leads to a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…However, microglial cells do not express functional Cav1.2 channels [ 150 ], thus the anti-inflammatory effects of these drugs are likely mediated by their block on other cell types [ 72 ]. Recently, it was found that animals injected with nimodipine during CPZ-induced demyelination displayed a reduced astrocyte and microglia activation and proliferation as well as a faster and more efficient brain remyelination [ 74 ]. Cav1.2 channels are not present in mature OLs [ 96 , 104 ], but they are expressed by OPCs where they are essential for maturation [ 100 , 101 ], as mentioned above.…”
Section: Voltage-gated Channels In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…However, microglial cells do not express functional Cav1.2 channels [ 150 ], thus the anti-inflammatory effects of these drugs are likely mediated by their block on other cell types [ 72 ]. Recently, it was found that animals injected with nimodipine during CPZ-induced demyelination displayed a reduced astrocyte and microglia activation and proliferation as well as a faster and more efficient brain remyelination [ 74 ]. Cav1.2 channels are not present in mature OLs [ 96 , 104 ], but they are expressed by OPCs where they are essential for maturation [ 100 , 101 ], as mentioned above.…”
Section: Voltage-gated Channels In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…This chemical probe provides an alternative to current methods that rely on immunological techniques or molecular biology modifications to monitor protein localization. It also paves the way to investigate the role of LTCC dynamics in calcium events in neurological disorders, e.g., Alzheimer’s, Parkinson’s, and multiple sclerosis [36, 63–67].…”
Section: Resultsmentioning
confidence: 99%
“…The diameter of axons and their fibre bundles were measured. The g-ratio (the diameter of fibre bundle of axon versus axon diameter) was calculated to evaluate the demyelination of axons [ 53 ].…”
Section: Methodsmentioning
confidence: 99%